THE DILEMMA OF PRODUCTIVE WAQF: INSTITUTIONAL STRENGTHENING OR DISTRIBUTION PUBLIC WELFARE? ANALYSIS AT THE SYUHADA GRAND MOSQUE FOUNDATION IN YOGYAKARTA - Muhammad Azkia Pasya; Mohammad Jamaludin; Maely Permatasari; Akbar Nur Wahid; Muhammad Taufik Hidayat (Universitas Islam Indonesia, 2026)
Purpose – This study aimed to analyze the implementation of productive waqf at the Syuhada Grand Mosque Foundation (YASMA) in Yogyakarta using the maqāṣid al-sharīʿah perspective with a systems approach. The analysis focuses on evaluating waqf governance, compliance with regulations, the mechanism for distributing benefits, and their impact on community welfare. Methods – This study uses a qualitative approach with a case study on the management of productive waqf at the Syuhada Grand Mosque Foundation in Yogyakarta. Research data were obtained through documentation, observation, and interviews with waqf managers. The collected data were analyzed descriptively and analytically using a system-based maqāṣid al-sharīʿah framework. Findings – The results of the study show that productive waqf at YASMA is managed in the form of cash waqf and land waqf focused on the construction and development of infrastructure, such as the Syuhada Center, Islamic Educational Institutions, and Dormitories. Waqf management contributes to institutional sustainability, but it is still internal in nature and does not provide broad economic benefits to the surrounding community. The practice of waqf management is carried out through the principles of openness and multidimensionality by simultaneously integrating the objectives of Sharia (Islamic law), social, and economic aspects. However, the utilization of waqf still tends to be oriented towards strengthening internal institutions (protective-institutional) and has not yet fully developed into a model of social transformation that expands the distribution of community welfare (maqāṣid 'amah). Research contribution/limitations – This study offers a more comprehensive community-based model of waqf institutional governance, benefit distribution, and its impact on community welfare. The limitations of this study lie in the case studies of local institutions; therefore, the findings cannot be fully generalized. Originality/value – This study provides added value by presenting an empirical analysis of productive waqf management based on mosques and its contribution to social welfare.